Exploring the Therapeutic Benefits of Silymarin Herbal Extract as a Supplement to Pulmonary Tuberculosis Treatment: A Comprehensive Review from Laboratory to Clinical Trials - Muhammad I. D. Rakasiwi; Muhammad Taufik; Gusti C. Pamungkas; Muhammad Z. B. Amaanullah; Idham R. Dewantara (Medical Scope Journal, 2024)
Abstract: Indonesia is ranked second in the number of tuberculosis (TB) cases with an incidence rate of 300 per 1000 population. A combination of antibiotics with a minimum six-month-administration regimen is an effective first line of TB treatment. Silymarin (Sm) is a plant extract which is known to have hepatoprotective and anti-microbial effects. This literature review aimed to discuss the potential of Sm in pulmonary TB treatment, starting from laboratory studies to clinical trials in humans. Studies on the use of Sm in tuberculosis literatures were obtained from a rapid systematic search in Pubmed and ScienceDirect databases. Supporting articles were searched based on specific keywords with inclusion criteria. The in vitro test showed immunomodulatory and bactericidal capacities of Sm against Mycobacterium tuberculosis. The in vivo test of Sm administration showed that Sm was able to increase the percentage of macrophage cells expressing the cytokines NF-κB and IFN-β. Sm had a bactericidal effect at levels >50 μM. The hepatoprotective character of Sm could prevent the increase in liver enzymes in mice receiving anti-TB drugs. Clinical trials showed that administration of Sm could prevent anti-tuberculosis drug hepatoxicity. In conclusion, silymarin has the potential to be an adjuvant therapy for the treatment of anti-TB drug-sensitive or resistant tuberculosis, as well as protection against the hepatotoxic properties of anti-TB drugs. Keywords: tuberculosis; silymarin; supplementation therapy; antituberculosis therapy